A cell-based, high-throughput homogeneous timeresolved fluorescence assay for the screening of potential κ-opioid receptor agonists - WANG Yue; YAN Ming; ZHENG Guang-yao; HE Ling; YANG Huan (Acta Pharmacologica Sinica, 2016)
Yue WANG1, #, Ming YAN2, #, Guang-yao ZHENG3, #, Ling HE1, *, Huan YANG1 1Department of Pharmacology, China Pharmaceutical University, Nanjing 210009, China; 2National Drug Screening Laboratory, China Pharmaceutical University, Nanjing 210009, China; 3Institute of Chemistry and Industry of Forest Products, National Engineering Laboratory for Biomass Chemical Utilization; Key and Open Laboratory of Forest Chemical Engineering, Key Laboratory of Biomass Energy and Material, Nanjing 210042, China Aim: The aim of this study was to identify κ-opioid receptor (KOR) agonists from a library of 80 000 small-molecule compounds and provide the experimental basis for the development of new analgesic candidates. Methods: The cell-based, high-throughput screen for human KOR agonists was based on the LANCETM cAMP assay. Preliminary structure-activity relationship (SAR) analysis was applied according to the compounds’ structures. An acetic acid twisting experiment was used to verify the pharmacodynamics. Results: In total, 31 compounds were identified as KOR agonists after preliminary and secondary screening. Of these compounds, five demonstrated significant KOR-stimulating activity that was comparable to U-50,488, a selective KOR agonist. The EC50 values for I-7, I-8, I-10, II-5, and II-8 were 13.34±1.65, 14.01±1.84, 9.57±0.19, 14.94±0.64, and 8.74±0.72 nmol/L, respectively. Based on SAR studies, the stimulating activity of compounds with 5-phenyl-7-(trifluoromethyl)-4,5,6,7-tetrahydropyrazolo [1, 5-a] pyrimidine (group I) and 3,4-dimethoxy-N-(2-oxoethyl)-N-p-tolylbenzenesulfonamide (group II) parent structures were higher than the compound with a 5-hydroxy-2-methylbenzofuran-3-carboxylic acid (group III) parent structure. Pharmacodynamic experiments indicated that 20–40 μg/kg ip of compounds I-10 and II-8 significantly decreased the number of writhes induced by acetic acid; this finding is consistent with the SAR studies. Furthermore, the analgesic effects of compounds I-10 and II-8 were significantly antagonized in the presence of the selective KOR antagonist nor-BNI. Conclusion: These findings collectively indicate that compounds I-10 and II-8 exhibit significant analgesic activities, providing evidence, at least in part, for their clinical application as new analgesic drugs. Keywords: κ-opioid receptor agonists; LANCETM cAMP assay; high-throughput screening; structure-activity relationship; writhing test This project was supported by the National 12th Five-year Plan for “Major Scientific and Technological Special Project for Significant New Drugs Creation” project of “Novel G protein-coupled receptor targeted drug screening system and key technology research” (No 2012ZX09504001-001); the Program for New Century Excellent Talents in University (No NCET-10-0817); the Major Scientific and Technological Special Project of Guangdong Province (No 2012A080201005) and the Fundamental Research Funds for the Central Universities (Nos JKZ2009005 and JKY2011052). # These authors contributed equally to this work. * To whom correspondence should be addressed. E-mail heling92@hotmail.com Received 2013-09-27 Accepted 2014-01-22